The terrorism-finance nexus contingent on globalisation and governance dynamics in Africa - Simplice Asongu; Tii Njivukuh Nchofoung (African Governance and Development Institute (AGDI), 2021)
This study empirically verifies the effect of terrorism on financial development and how globalisation and governance modulate the incidence of terrorism on financial development in Africa. Two terrorism indicators are adopted for this study, namely, the: number of terrorism incidences and number of terrorism deaths. The methodology involves the pooled data technique running from 1996-2018 for 34 African countries. The results from the POLS, Driscoll-Kraay and the Newey-West standard error corrections show that terrorism is detrimental to financial development. From the interactive regressions, three major tendencies are apparent. First, terrorism dynamics consistently have an unconditional negative effect on financial development. Second, the globalization and government dynamics modulate the terrorism dynamics to broadly induce a negative net effect on financial development. Third, policy thresholds at which the modulating variables reverse the net effect on financial development from negative to positive are: (i) 71.61572 trade (% of GDP) and 13.97872 FDI (% of GDP) for the incidence of terror and (ii) 1.16201 trade (% of GDP) for terror deaths. The computed thresholds make economic sense and worthwhile in terms of policy implications because they are within statistical range. The result is robust to alternative measures of terrorism and financial development. Policy implications are discussed.
Keywords: D74; G28; F65; P37; C52; 330; terrorism; financial development; globalisation; governance; Pooled data